2020
DOI: 10.3389/fpubh.2020.00498
|View full text |Cite
|
Sign up to set email alerts
|

Travel Time to Health Facilities as a Marker of Geographical Accessibility Across Heterogeneous Land Coverage in Peru

Abstract: To better estimate the travel time to the most proximate health care facility (HCF) and determine differences across heterogeneous land coverage types, this study explored the use of a novel cloud-based geospatial modeling approach. Geospatial data of 145,134 cities and villages and 8,067 HCF were gathered with land coverage types, roads and river networks, and digital elevation data to produce high-resolution (30 m) estimates of travel time to HCFs across Peru. This study estimated important variations in tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 40 publications
1
46
0
1
Order By: Relevance
“…For example, those working in healthcare could secure adequate antenatal care, those working with poor or vulnerable populations could secure access to what mothers need for a healthy pregnancy (e.g., diet, education, and prevention of acute diseases), and those working in transportation could secure safe routes and means to access timely antenatal and maternal healthcare, particularly in rural settings. [49] The equiplots also showed that the birthweight indicators would be worse for mothers aged <19 years; this observation agrees with the literature on the subject. [ 50 , 51 ] Regarding low birthweight prevalence, the youngest mothers were closely followed by those aged 36+ years, which has also been documented before.…”
Section: Discussionsupporting
confidence: 87%
“…For example, those working in healthcare could secure adequate antenatal care, those working with poor or vulnerable populations could secure access to what mothers need for a healthy pregnancy (e.g., diet, education, and prevention of acute diseases), and those working in transportation could secure safe routes and means to access timely antenatal and maternal healthcare, particularly in rural settings. [49] The equiplots also showed that the birthweight indicators would be worse for mothers aged <19 years; this observation agrees with the literature on the subject. [ 50 , 51 ] Regarding low birthweight prevalence, the youngest mothers were closely followed by those aged 36+ years, which has also been documented before.…”
Section: Discussionsupporting
confidence: 87%
“…Health authorities should also improve structural barriers. For example, if commuting to the healthcare centre is a barrier to seek care and receive treatment [14] , other options must be considered like tele-medicine along with remote devices [15] , and community visits.…”
Section: Discussionmentioning
confidence: 99%
“…Second, limited access to remote areas in the Amazon region prevents continuous health care access to indigenous communities, thus the malaria caseload is an underestimate. Low geographic accessibility and travel time have been found to be barriers to reaching remote health facilities ( 35 ). Third, some reports have indicated that mosquito activities such as host-seeking behavior were influenced by wind speed affecting human CO 2 dispersion, and other studies reported that the mosquito movement depends on wind direction ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…For malaria, the diagnosis is carried out exclusively by MoH. However, health access is still deficient in indigenous and rural communities in the Peruvian Amazon, mainly due to transportation and monetary barriers ( 34 , 35 ). Approximately 83.3% of the population had informal employment since the most common economic activities are based on agriculture, fishing, and mining ( 32 ).…”
Section: Methodsmentioning
confidence: 99%